2023
DOI: 10.1186/s13287-023-03497-z
|View full text |Cite
|
Sign up to set email alerts
|

Application of mesenchymal stem cells for anti-senescence and clinical challenges

Yaping Wang,
Tianyun Gao,
Bin Wang

Abstract: Senescence is a hot topic nowadays, which shows the accumulation of senescent cells and inflammatory factors, leading to the occurrence of various senescence-related diseases. Although some methods have been identified to partly delay senescence, such as strengthening exercise, restricting diet, and some drugs, these only slow down the process of senescence and cannot fundamentally delay or even reverse senescence. Stem cell-based therapy is expected to be a potential effective way to alleviate or cure senesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 261 publications
0
2
0
Order By: Relevance
“…Various in vitro studies have demonstrated the safety, efficacy, and therapeutic potential of exosomes in various diseases including cancers, neurodegenerative disorders, cardiovascular diseases, and orthopedic conditions. 90 3.4. Mitochondrial Transfer.…”
Section: Senolytics and Senomorphicmentioning
confidence: 99%
See 1 more Smart Citation
“…Various in vitro studies have demonstrated the safety, efficacy, and therapeutic potential of exosomes in various diseases including cancers, neurodegenerative disorders, cardiovascular diseases, and orthopedic conditions. 90 3.4. Mitochondrial Transfer.…”
Section: Senolytics and Senomorphicmentioning
confidence: 99%
“…Exosomal cargo plays a pivotal role in diagnosing and executing therapeutic roles while regulating disease processes. Various in vitro studies have demonstrated the safety, efficacy, and therapeutic potential of exosomes in various diseases including cancers, neurodegenerative disorders, cardiovascular diseases, and orthopedic conditions …”
Section: Therapeutic Strategies Targeting Mscs Senescencementioning
confidence: 99%